The Legal Discourse of Al-Ādah Muhakkamah on Mappanini Bosi Tradition in Bone Regency - Widjaja, Abdi; Mahmusin, Muhammad Arash bin; Abdulrazak, Fahri Asyudi; Nazaruddin, Rezkiawati (Universitas Islam Negeri Alauddin Makassar, 2023)
The inhabitants of Pattiro Village, situated within the Dua Boccoe Subdistrict of Bone Regency, are renowned for their customary practice known as